Evaluasi Dampak Penerapan Teknologi Drip Irrigation Berbasis Internet Of Things Terhadap Produksi Usahatani Cabai Merah Di Desa Cipanjalu - syahidah, Rahmah; Netraning Pertiwi, Widhi; Sutandi, Agus (Jurnal Ragam Pengabdian, 2026)
P This study aims to evaluate the impact of technology adoption on red chili pepper farm production in Cipanjalu Village, using changes in farm income as an indicator of economic benefits.. The study employed a quantitative approach involving 70 respondents, comprising 35 farmers who had adopted the technology and 35 who had not. Data were collected through observation, interviews, and questionnaires. The impact of technology adoption was analyzed using the Difference-in-Differences method. The results of the Difference-in-Differences analysis show that the adoption of this technology has a positive and significant effect on increasing the income from red chili farming. These findings indicate that the adoption of this technology also supports more efficient water use and better crop management, thereby potentially increasing production and farmers’ well-being.